Fiscal federalism and economic development in Ethiopia: a moderating effect analysis of macroeconomics instability - Million Adafre Bushashe; Yitbarek Takele Bayiley (Cogent Social Sciences, 2024)
This study aimed to scrutinize the association between fiscal federalism and economic development in Ethiopia. By employing ten sub-national government (SNG) data over the period 2005–2018, the study uses the Partial Least Square Structural Model (PLS-SEM). The study proved that revenue decentralization and fiscal incentives significantly enhance economic development. Nevertheless, expenditure decentralization significantly deteriorates economic development. Moreover, economic instability has an adverse moderating role in the contribution of revenue decentralization to economic development. However, it has no role in the indirect effect of expenditure and fiscal incentives on economic development. The control variable (economic category) shows that SNGs in emerging economies have significantly lower economic development than SNGs in advanced economies. The most important inference is that the center should review the devolution of expenditure responsibility and autonomy to SNGs. Hence, the ideas of fiscal federalism contend that the execution of expenditure decentralization positively affects SNGs’ economic development. The SNG should be more assertive in controlling the local economy since the national government is limited in overseeing development execution in the areas. The study attempts to combine the two theoretical perspectives of fiscal federalism and examines the direct effect of fiscal federalism on economic development and its indirect influence through the moderating variable (i.e. macroeconomic instability). Therefore, it contributes to the prevailing literature on fiscal federalism.